The expression problem in platform-aware programming - Carvalho Junior, Francisco Heron de (Anais do Simpósio Brasileiro de Linguagens de Programação (SBLP); 2024: Anais do XXVIII Simpósio Brasileiro de Linguagens de Programação, 2024)
Platform-aware programming involves making assumptions about specific features of the target execution environment to improve performance. We restate a fundamental problem in software extensibility called The Expression Problem for platform-aware programming to show how a solution based on dynamic multiple dispatch over platform types may improve such a performance engineering practice.